The Uyghurian Version of the KA-SI Empathic Tendency Scale-Adolescent Form: Validity and Reliability - Yusupu, Reziwanguli; Siyez, Diğdem Müge; KAYA, ALİM (Cengiz Alyılmaz, 2022)
The aim of this study was to examine the factorial validity, measurement invariance across sex, and reliability of a Uyghurian version of the KA-SI Empathic Tendency Scale-Adolescent Form (KA-SI AF) among adolescents in Xinjiang, China. A total of 331 middle and high school students (198 girls, 133 boys) were included in the sample. Research data was collected via KA-SI AF and demographic questionnaire. Confirmatory factor analyses supported a two-dimensional structure (cognitive and emotional). Multi-group CFA supported measurement invariance across sex groups. The Uyghur form of KA-SI AF yielded excellent reliability values from .84 to .90. Findings suggest that Uyghur version of the KA-SI AF was valid and reliable measure of empathic tendency suitable for middle and high school students.
KA-SI Empatik Eğilim Ölçeği-Ergen Formu’nun Uygurca Versiyonu: Geçerlik ve Güvenirlik
Keywords: Empathic Tendency Scale; Validity; Reliability; Uyghurian Version